Kekuatan Pembuktian Suatu Surat Pernyataan Bermaterai Dalam Sengketa Keperdataan di Pengadilan - Evi, Evi Evi (Morality: Jurnal Ilmu Hukum; Vol 7 No 1 (2021): Morality :Jurnal Ilmu HukumDO - 10.52947/morality.v7i1.192, 2021)
In every civil dispute in the court, it is often to find a statement letter with a seal on it, which is used in other to proving or claiming a person's rights, nevertheles how is the legality in a civil trial? This writing is conducted in order to describe the evidentiary force of a letter made on a stamp duty through normative legal research method by examining problems normatively using a conceptual approach. A stamped statement is a privately made deed as evidence and filed in a civil dispute in court. It can have the full evidentiary force as long as the party in the letter acknowledges its veracity. Keywords: Evidence, Stamped, Civil Dispute